2009
DOI: 10.25182/jgp.2009.4.2.83-92
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan, Sikap, Dan Praktek Asi Ekslusif Serta Status Gizi Bayi Usia 4-12 Bulan Di Pedesaan Dan Perkotaan

Abstract: The main aim of this study was to compare breastfeeding knowledge, attitude, and practice and infants nutritional status between rural and urban areas. In this cross-sectional study, Desa Jayabakti, Kabupaten Sukabumi represents rural area, while Kelurahan Kedung Jaya, Kota Bogor represents urban area. Samples were 31 mothers-infants in each area who were selected by simple cluster sampling method. The differences between two areas were analyzed with the independent t-test, chi-square test, and Fisher's exact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
2
0
3
Order By: Relevance
“…Such persuasion was higher in urban than rural areas. 17 Changes in sociocultural values in urban areas have resulted in breastfeeding considered to be old- fashioned and traditional. Traditional breastfeeding habits (without bottled and formula milk) in a population were likely to change due to contact with the modern world, leading to changes in values and beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Such persuasion was higher in urban than rural areas. 17 Changes in sociocultural values in urban areas have resulted in breastfeeding considered to be old- fashioned and traditional. Traditional breastfeeding habits (without bottled and formula milk) in a population were likely to change due to contact with the modern world, leading to changes in values and beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…In this research it was concluded that mothers with low levels of knowledge so that mothers do not share exclusive breastfeeding and have babies with poor nutritional status as much as 15.1%. (Rachmadewi & Khomsan, 2009) in her research in 2019 in her research, Knowledge, behavior, and exclusive breastfeeding practice and nutritional status of children aged 4-12 months in rural and urban areas, it is concluded that the knowledge of mother's nutrition has a positive relationship with the nutritional behavior of mothers in rural or urban areas. Aspects that are significantly related to the knowledge of nutrition for mothers in rural areas are the mother's age, work status, and previous breastfeeding experience.…”
Section: Mulyadimentioning
confidence: 99%
“…Pola pengasuhan gizi yang baik ini dapat dipengaruhi adanya program dari puskesmas yaitu kelas ibu balita, dalam kegiatan kelas ibu balita ibu mendapatkan pengetahuan tentang gizi balita, ibu juga dapat berdiskusi, tukar pendapat, tukar pengalaman akan pemenuhan pelayanan kesehatan, gizi dan stimulasi pertumbuhan dan perkembangan balita yang dibimbing oleh bidan desa dan petugas gizi puskesmas, sehingga dirumah ibu dapat menciptakan pola asuh yang baik bagi balita. Meskipun sebagian besar pola pengasuhan balita positif akan tetapi masih terdapat balita dengan gizi kurang, gizi buruk, gizi lebih dan obesitas hal tersebut disebabkan karena perbedaan pola pikir, pendidikan ibu, sosial ekonomi dan budaya setempat [17].…”
Section: Hubungan Pengetahuan Gizi Ibu Dengan Status Gizi Balita DI P...unclassified